Expression of cyclooxygenase-2(COX-2) and cyclin dependent kinase 1B (CDKN1B/p27Kip1⁯) in human prostatet adenocarcinoma - Md Roduan, Mohd Rohaizad (2011)
Prostate adenocarcinoma is one of the most common forms of malignancy occurring in the Malaysian male population. Inflammation has been identified in many studies to play key roles in the process of carcinogenesis. Inflammation is responsible for prompting angiogenesis, enhancing cellular motility and increasing resistance to apoptosis. Cyclooxygenase-2 (COX-2) is an enzyme that converts arachidonic acid into proinflammatory prostaglandins and other eicosanoids. In addition, COX-2 is also highly expressed in a wide number of human cancers including prostate adenocarcinoma. Moreover, loss of Cyelin dependent kinase inhibitor IB (p27Kip) expression has been implicated in the malignant development in many human cancers. p27Kip) is a gene that encodes protein for cell cycle regulation generally, and controls the cell cycle progression at G) phase specifically. Low expression ofp27Kip) has been associated with a poor prognosis in malignant tumours, including breast, gastric and prostate carcinoma. The objectives of this study were to determine the expression level of COX-2 and p27Kipl in different types of prostate tissue and to relate the association with the clinicopathological parameters. p27Kipl (VI09G) polymorphism frequency in prostate adenocarcinoma was also determined to assess its relationship with advance prostate cancer susceptibility. Paraffin-embedded prostatic tissue (n = 263) was obtained from the Pathology Department of Hospital Kuala Lumpur. The mean age of the patients is 64.54 ±10.79 years. The tissue retrieved consisted of 63 normal prostate tissue samples, as well as 100 each for benign prostatic hyperplasia (BPH) and prostate adenocarcinoma (PCa). COX-2 expression was performed using standard immunohistochemistry methods. Anti-human COX-2 monoclonal mouse primary antibody was used in a 1:]00 dilution, whereas the anti-human p27Kipl monoclonal mouse primary antibody was used in a dilution of 1:50. For each sample, the extent and intensity of staining with COX-2 antibody was graded on a scale from 0 to 4+. Staining was classified as 0 (no expression), I+ (weak expression), 2+ (moderate expression), 3+ (strong expression) and 4+ (very strong expression). The results showed that, 561100 PCa samples showed strong COX-2 expression (P=O.OOO), in comparison 161100 samples of BPH (P=O.OO 1), while weak COX-2 expression was observed in all 63 normal samples. Very strong expression for p27Kipl was seen in 62/63 normal prostate tissue samples and 771100 BPH samples (P=O.OOO), while 39/100 PCa samples exhibited weak p27Kipl expression and 25 of the rest had no expression (P=O.OOO). Next, to confirm the accuracy of staining, we further analysed selected samples by semiquatitative reverse transcriptase PCR (RTPCR) method on COX-2 and p27Kipl genes. This RT-PCR analysis, COX-2 expression was detected in high Gleason scores of 8 and 9, which were 2.01 and 2.17-fold respectively higher compared to normal tissue. BPH displayed only 1.04-fold higher COX-2 expression than normal tissue. Significant down-regulation of p27KipJ was observed in Gleason scores 7, 8 and 9 which were less than O.5-fold in changes compared to normal prostatic tissue. No significant p27KipJdown-regulation was observed in BPH samples compared to normal samples. PCR-RFLP was used to investigate p27KipJ polymorphism using Bgl1 restriction enzyme. PCR-RFLP analysis showed that distribution of genotypes were not statistically significant between PCa and normal prostate, whereby the genotypes VV and VG were observed more frequently in PCa and normal prostate, while GG genotype was not found in any PCa or normal samples. The results of this study, suggest that COX-2 overexpression and p27KipJ down-regulation may play a role in the progression of prostate adenocarcinoma. Therefore, expression of COX-2 and p27KipJ as potential therapeutic targets for prostate cancer should be evaluated further.